Evidence of Jet Activity from the Secondary Black Hole in the OJ 287 Binary System - Valtonen, Mauri J.; Zola, Staszek; Gupta, Alok C.; Kishore, Shubham; Gopakumar, Achamveedu; Jorstad, Svetlana G.; Wiita, Paul J.; Gu, Minfeng; Nilsson, Kari; Marscher, Alan P.; Zhang, Zhongli; Hudec, Rene; et al. (Institute of Physics Publishing, 2025)
We report the study of a huge optical intraday flare on 2021 November 12 at 2 a.m. UT in the blazar OJ 287. In the binary black hole model, it is associated with an impact of the secondary black hole on the accretion disk of the primary. Our multifrequency observing campaign was set up to search for such a signature of the impact based on a prediction made 8 yr earlier. The first I-band results of the flare have already been reported by Kishore et al. (2024). Here we combine these data with our monitoring in the R-band. There is a big change in the R-I spectral index by 1.0 +/- 0.1 between the normal background and the flare, suggesting a new component of radiation. The polarization variation during the rise of the flare suggests the same. The limits on the source size place it most reasonably in the jet of the secondary BH. We then ask why we have not seen this phenomenon before. We show that OJ 287 was never before observed with sufficient sensitivity on the night when the flare should have happened according to the binary model. We also study the probability that this flare is just an oversized example of intraday variability using the Krakow data set of intense monitoring between 2015 and 2023. We find that the occurrence of a flare of this size and rapidity is unlikely. In machine-readable Tables 1 and 2, we give the full orbit-linked historical light curve of OJ 287 as well as the dense monitoring sample of Krakow.